2018
DOI: 10.1093/ecco-jcc/jjy212
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Histopathological Features at Diagnosis of Very Early Onset Inflammatory Bowel Disease

Abstract: Background and Aims: Children with very early onset inflammatory bowel disease [VEO-IBD] represent a unique cohort, often with a severe phenotype that is refractory to conventional medications, and some cases have underlying primary immunodeficiencies. Previous work has identified distinct histopathological patterns in the gastrointestinal tract in patients with primary immunodeficiencies. The aim of this study is to characterise the diagnostic histological findings in patients with VEO-IBD as compared with ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 27 publications
2
52
2
Order By: Relevance
“…The reasons why eosinophils seem to be more active in younger patients and also during remission are not known and, as yet, have been largely uninvestigated. It has been reported that colonic eosinophilia is more prevalent in younger than in older children diagnosed with IBD or other colonic diseases [45,46]. Furthermore, tissue eosinophilia seems to be a dominant feature of subclinical histological inflammation for patients with IBD in remission [47], which might be more prevalent in young patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons why eosinophils seem to be more active in younger patients and also during remission are not known and, as yet, have been largely uninvestigated. It has been reported that colonic eosinophilia is more prevalent in younger than in older children diagnosed with IBD or other colonic diseases [45,46]. Furthermore, tissue eosinophilia seems to be a dominant feature of subclinical histological inflammation for patients with IBD in remission [47], which might be more prevalent in young patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical follow-up data was available for 202/212 visits (95.3%) of patients with IBD. The median (IQR) follow-up time was 48 (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) months. The total event rate was 94/202 (46.5%).…”
Section: Fecp Is a Prognostic Biomarker In Young Patients With Ibdmentioning
confidence: 99%
“…Classic IBD shows granulomas and fissures in Crohn's disease, and crypt abscesses, glandular architectural distortion, and pseudo polyps in ulcerative colitis. 15 Apoptosis is a key feature in VEO-IBD 16 and STAT3 and CTLA-4 mutations have been described as monogenic causes of VEO-IBD. 15 Clinically, VEO-IBD occurs in children younger than 6 years (3 of our 4 patients are older), and histopathologically, in addition to apoptosis, there is generally significant eosinophilia (including eosinophilic crypt microabscesses) and to a lesser extent villous blunting.…”
Section: Discussionmentioning
confidence: 99%
“…IBD, consisting of Crohn’s disease and ulcerative colitis, afflicts more than 3.5 million patients in the Western hemisphere with increasing incidence over the last five decades [ 3 ]. IBD is characterized by chronic, unrelenting intestinal inflammation, villus blunting and crypt hypertrophy that leads to malabsorption of fluid, electrolytes and nutrients as well as secretion of fluid and electrolytes [ 28 , 29 , 30 , 31 , 32 ]. This in IBD results in its most common and disabling symptoms, diarrhea, malnutrition, weight loss and in the pediatric population, a failure to thrive.…”
Section: Discussionmentioning
confidence: 99%